Marcas da escritura oralizada em Sagarana - Araújo, Roberta Duarte de (2008)
This work presents a surveyabout the short stories of Sagarana. first book by Guimarães Rosa, publishedin 1946, and that marked the Brazilian litterature definitely, since we are in front of a new construction of the language, linked to the establishment of a new Portuguese, trough the association between the cult speech and the speech from the sertão, always with a pretence sensitivity that rouses when joins archaisms, neologisms, regional expressions and literary language. Among the nine short stories that made up the work, we will select the following ones, to be analysed: "O Burrinho Pedrês", Traços Biográficos de Lalino Salãthiel ou A volta do marido pródigo , "São Marcos" and A hora e vez de Augusto Matraga". Among the hypothesis that organize and surround this work, we will approach the narrative aesthetics, the creative process and the orallity, i.e., how Rosa trans1ate the oral world, rescuing the archaizing speech in the written narrative construction.We will choose for the establishment of developed questions in this ressearch the theories of Paul Zumthor, Câmara Cascudo, Sílvio Romero, Antonio Candido and Alfredo Bosi, among others. Therefore, we will see, through the narrative reading, how the popular parlances are used, which they are linked. The citations that show the popular tradition presence will be pointed out, through anecdotes, folk songs, legends, myths, folktales and proverbs. Therefore, we, readers, will see the popular tradition presence, that will show itself, and the Rosa's thinking will be known through language art, what is the result of the writer's deliberate choice. We will see the popular experience turned to art